2006
DOI: 10.1111/j.1747-6593.2006.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Operating strategies for variable‐flow sequencing batch reactors

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The design and operation of SBR must consider the biological process requirement and the hydraulic regime to maintain the quality of treatment. The fill strategy and the cycle time control are important factors to be taken into consideration while optimizing the treatment process 34. While designing the fill strategy for the treatment of toxic wastewater, its biodegradability and concentration should be taken into account.…”
Section: Sbr: Different Modes Of Operationmentioning
confidence: 99%
“…The design and operation of SBR must consider the biological process requirement and the hydraulic regime to maintain the quality of treatment. The fill strategy and the cycle time control are important factors to be taken into consideration while optimizing the treatment process 34. While designing the fill strategy for the treatment of toxic wastewater, its biodegradability and concentration should be taken into account.…”
Section: Sbr: Different Modes Of Operationmentioning
confidence: 99%
“…Switching to the next phase shortly after the detection of the reaction endpoint provides an optimum solution for both the process performance and the economies of the plant. For the SBR process, Bungay et al (2007) demonstrated that the flow-proportional cycle times control strategy use the treatment volume more efficiently than fixed cycle times. In our study, the on-line monitoring ORP and pH profiles indicated accurately the biochemical reaction procedures for anaerobic P-release, nitrifying denitrification and P-uptake.…”
Section: Establishing a Real-time Control Strategy For More Efficientmentioning
confidence: 99%
“…A laboratory-scale study by indicated that A 2 N-SBR showed steady phosphorus and nitrogen removals which enabled the removal of 15mg P/L and 105mg N/L at the expense of only 400 mg COD/L acetate (HAc), i.e. the optimal influent ratio was as low as 3.4 g COD/g N. Additionally, A 2 N-SBR integrates two SBRs which means it is easy to change operations, such as cycle times and flow rates (Irvine et al, 1997;Del Solar et al, 2004;Bungay et al, 2007). Therefore, the A 2 N-SBR has higher flexibility and has been regarded as effective, especially for small wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%
“…In an SBR, the retention time, the duration of the aeration and anoxic phases, the settling time, and other conditions can be easily fitted to variations on load quality as well as effluent requirements. When properly designed and operated, SBRs offer important advantages over continuous processes, not only because of its efficiency and economical aspects, but also because of its small footprint and high flexibility and operation range …”
Section: Case Studymentioning
confidence: 99%